Design of General Election in Indonesia - Muhammad Syafei; Muhammad Rafi Darajati (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2020)
The 2019 general elections in Indonesia have been held differently from the previous period. The 2019 general elections held simultaneously five boxes. This article discusses how the implementation of the 2019 general election and how the rather election should be carried out in the future. The author concludes that the implementation of simultaneous general elections in 2019 caused tremendous complexity for participants, voters, and organizers. The complexity and constraints that occur make the selection process not run well and less efficient and effective time spent. Then for the coming period, the elections should be carried out using the design of simultaneous national elections and simultaneous regional elections. In the simultaneous national election, it held to elect the President and Vice President, members of the House of People’s Representative, and members of the Regional Representative Board. Then in the simultaneous regional election, it held to elect the Governor, Regent/ Mayor, Provincial Legislative Council, and Regency/ City Legislative Council.